Germinación de semillas de Ficus insipida (Moraceae) defecadas por tucanes (Ramphastos sulfuratus) y monos araña (Ateles geoffroyi) - Domínguez-Domínguez, Laura E. (2006)
To test the null hypothesis that two vertebrate fructivores, toucans (Ramphastos sulfuratus) and spider monkeys (Ateles geoffroyi), are equally specialized in germinating Ficus insipida seeds after these have passed through their digestive tracts, we fed fruits to captive individuals. We extracted seeds from feces and placed them on filter paper in petri dishes under controled light, temperature and humidity. Control seeds had not passed through a digestive tract. We found that a greater proportion of seeds from A. geofroyi (65% ) germinated (R.sulfuratus: 4%). The germinative value was also greater in seeds from monkey feces (rate=13.76; toucan 0.046; control group 0.172). If, despite individual variability of seeds and dispersers, future studies continue to show that A. geoffroyi favors germination more (maybe because of a longer digestion time), this would indicate that diet specialization is not necessarily related to dispersal efficiency.